2015
DOI: 10.1155/2015/561293
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Unconfined Compressive Strength of Basalt Fiber Reinforced Clay Soil

Abstract: In order to study the mechanism and effect of basalt fiber reinforced clay soil, a series of unconfined compressive strength tests conducted on clay soil reinforced with basalt fiber have been performed under the condition of optimum water content and maximum dry density. Both the content and length of basalt fiber are considered in this paper. When the effect of content is studied, the 12 mm long fibers are dispersed into clay soil at different contents of 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, and 0.35%. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Vidal first proposed the concept of soil modification in the 1960s [1]. This technology has been developed rapidly and is now widely used in roadbeds, retaining walls, anti-seismic infrastructures, and other fields [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Vidal first proposed the concept of soil modification in the 1960s [1]. This technology has been developed rapidly and is now widely used in roadbeds, retaining walls, anti-seismic infrastructures, and other fields [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the basalt fibers were closely surrounded by soil particles, soil matrix, and cementitious products in Figure 21(c). With the basalt fiber content of 0.6%, the randomly distributed basalt fibers and cemented soil matrix interact with each other and generate a stable internal space structure [27,42]. Consequently, the macroscale mechanical behaviors presented in previous sections have a maximum improvement of cement-fly ash-stabilized soil with 0.6% basalt fiber, which include the enhancements of static compressive strength, dynamic compressive strength, and energy absorption capacity.…”
Section: Microstructure Analysis Of Basalt Fiber-reinforced Cement-flmentioning
confidence: 95%
“…is is an evidence to certify that the excess basalt fiber has a negative effect on the improvement of dynamic compressive strength. e enhancement in dynamic compressive strength can be explained by the following reasons: (1) with the addition of basalt fiber, the interfacial bonding strength between fiber and soil matrix is enhanced [42]; (2) the formation of fiberhydration products-soil mixture provides a better adhesion among soil particles; (3) the stable three-dimensional fibersoil net generated inside the stabilized soil due to the bridging capacity of basalt fiber [27,42]; and (4) the good impact resistance of basalt fiber [27]. erefore, the cementfly ash-stabilized soil has a significant improvement in dynamic compressive strength with the inclusion of basalt fiber.…”
Section: Dynamic Compressive Strengthmentioning
confidence: 99%
“…e results indicated that with a fiber length of 10 mm and content of 1.0%, sisal fiberreinforced silty clay is 20% stronger than nonreinforced silty clay. Gao et al [12] performed a series of unconfined compressive strength tests on clay soil reinforced with basalt fibers under the condition of optimum water content and maximum dry density. Experimental results showed that basalt fibers can effectively improve the unconfined compression strength of clay soil.…”
Section: Introductionmentioning
confidence: 99%